DYNAMICAL PROPERTIES OF PLASMID DNA MOLECULE IN PULSE REGIME BY OPTICAL TWEEZERS - Trung, Thai Dinh (JOURNAL OF ADVANCES IN BIOLOGY, 2016)
The dynamical properties of the plasmid DNA molecule in the optical tweezers using pulsed Gaussian laser beam is investigated. The finite difference Langevin equation (FDLE) describing the dynamics of polystyrene microsphere linking to plasmid DNA molecule is presented. This FDLE is numerically solved to discuss the influence of parameters of pulsed Gaussian laser beam as peak intensity, duration on the dynamical properties of polystyrene microsphere. From the variances of position, velocity or all forces in pulsing time, the conditions to stretch a plasmid DNA molecule into stretching state, where the maximum stretched length is about its contour length are discussed and found out.